A National Survey on Congenital Hypothyroidism Newborn Screening in Pakistan - Sabeen Abid Khan FCPS, FRCPCH; Sommayya Aftab FCPS, FRCPCH; Yasir Naqi Khan MCPS; Mehrunnisa Yasir FCPS; Kashan Arshad FCPS; Noor ul Ain Mehak FCPS; Syed Kaleem ur Rehman MRCPCH; Abida Faiztalpur FCPS, MRCPCH; Shazia Bahar MRCPCH; Ayesha Abdul Razzaq FCPS; Sajjad Habibullah MD; Aamir Naseem FCPS; et al. (SAGE Publishing, 2024)
Objective . Congenital hypothyroidism (CH) is a treatable condition with a good outcome if diagnosed promptly. However, neonatal screening programs are not routinely available in developing countries in Pakistan. Method . To highlight the practices of newborn screening in Pakistan, an online survey was conducted. Google forms were circulated to national pediatric societies and hospitals. Results . Out of 341 respondents most were consultant pediatrician (n = 212, 62.17%) followed by residents (n = 80, 23.41%). Majority, (n = 309, 90.6%) believed it was essential to screen all newborns for CH. However, in practice only (n = 141, 41.3%) were offering screening. The most common reasons cited for not screening was the cost of test (n = 110, 32.2%), non-availability of testing services (n = 29, 8.5%) and lack of any implemented screening policies in the hospitals or national guidelines (n = 20, 5.8%). Differences in practice were also observed at provincial levels ( P  < .05). Conclusion . This survey highlights marked variation in CH newborn screening practices.